2021
DOI: 10.1007/978-3-030-80519-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reflective Measurement Models

Abstract: The goal of reflective measurement model assessment is to ensure the reliability and validity of the construct measures and therefore provides support for the suitability of their inclusion in the path model. This chapter introduces the key criteria that are relevant in reflective measurement model assessment: indicator reliability, internal consistency reliability (Cronbach’s alpha, reliability coefficient rhoA, and composite reliability rhoC), convergent validity, and discriminant validity. We illustrate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(161 citation statements)
references
References 15 publications
(19 reference statements)
2
73
0
1
Order By: Relevance
“…The results for CA and CR are presented in Table 3 for RB (0.874, 0.903), FoC (0.867, 0.893), WB (0.929, 0.937), respectively. this study found the reliability values to be in a satisfactory range (Hair et al, 2021).…”
Section: Measurement Modelmentioning
confidence: 64%
See 3 more Smart Citations
“…The results for CA and CR are presented in Table 3 for RB (0.874, 0.903), FoC (0.867, 0.893), WB (0.929, 0.937), respectively. this study found the reliability values to be in a satisfactory range (Hair et al, 2021).…”
Section: Measurement Modelmentioning
confidence: 64%
“…AVE values for RB, FoC and WB were 0.579, 0.546, 0.520, respectively (shown in Table 3). All the values were greater than the 0.50 threshold, which was acceptable (Hair et al, 2021).…”
Section: Convergent Validity (Ave)mentioning
confidence: 81%
See 2 more Smart Citations
“…Instead, the five hypothesized models and those generated in the AMOS program revealed that developed Model 5 is the bestfit structural model. However, not all manifest variables in the hypothesized model came out as predictors because the program removed some of these indicators during the statistical analysis for not meeting the standard outer loading requirement of greater than 0.70 Hair et al (2021a), Hair et al (2021b). Thus, the best-fit structural model of job performance is the combined effect of exogenous variables with specific manifest variables.…”
Section: Hypothesesmentioning
confidence: 99%